Net neutrality policy debate in Croatia : origins and policy actors - Brautović, Mato (Array, 2020)
This study examines the debate on net neutrality in the Croatian public sphere, its origin and connection to similar debates in the United States and the EU. The study also tries to answer who the policy actors that influence the NN debate are, how the policy-making process concerning this topic was carried out in Croatia, and what the role of the mainstream media is. Empirical data was collected from documents and posts regarding net neutrality found on government, media, NGO and industry websites. The findings show that there are two parallel debates on net neutrality and the character of the Croatian policy-making process: the debate that is going on in the mainstream and online media, where international topics and actors (the US, the EU) dominate, and the debate that is happening in the Croatian public sphere, which is carried out as part of panels and conferences (mainly organised by the Croatian Regulatory Authority for Network Industries). Although the mainstream media reported positively about net neutrality, they have failed to bring the process of policy-making and the corresponding debate closer to the general public, as was the case in the US or Western Europe.